Pengaruh Ekstrak Anggur Laut terhadap pH Lambung dan duodenum pada Rattus norvegicus Jantan yang Diinduksi Indometasin - Ardilon Raxel Faruwu; Riami Riami; Fitri Handajani (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2020)
Indomethacin is a nonsteroidal anti-inflammatory drugs (NSAIDs) that act to inhibit COX-1. The inhibition of COX-1 leads to inhibition of prostaglandin production. Prostaglandin is a regulator of gastric acid buffer secretion. Inhibition of prostaglandin decrease gastric and duodenum pH and damage the gastric and duodenum. Sea grapes (Caulerpa racemose var. cylindracea) are marcoalgae that contain flavonoids as antioxidants and anti-inflammatory. The aim of this study was to determine the effect of sea grapes on gastric and duodenum pH in rattus norvegicus induced by indomethacin. 32 male Rattus norvegicus were divided into 4 groups. Group K (-) without treatment. Group K (+) was induced by 30 mg/Kg BW indomethacin for 7 days. Group P1 was induced by 30mg/Kg BW indomethacin for 7 days followed by administration of 1g/100g BW sea grape extract for 14 days. Group P2 was induced by 30mg/Kg BW indomethacin for 7 days followed by administration of 2g/100g BW sea grape extract for 14 days. On the 29th day, rats were terminated, gastric and duodenal were isolated then the fluid pH was measured. One-way Anova test obtained p = 0,023. Post hoc test pH Gaster significantly different between group K (-) and K (+) (p= 0,005) and between group K (-) with P2 (p= 0,020). While in group K (+) with P1 and P2 there was no significant difference in pH.  Post hoc test of pH duodenum showed no differences in all group. The administration of sea grape extract did not show a differences of the gastric and duodenal pH significantly between rats induced by indomethacin.